2024
DOI: 10.1093/pnasnexus/pgae113
|View full text |Cite
|
Sign up to set email alerts
|

The maximum capability of a topological feature in link prediction

Yijun Ran,
Xiao-Ke Xu,
Tao Jia

Abstract: Networks offer a powerful approach to modeling complex systems by representing the underlying set of pairwise interactions. Link prediction is the task that predicts links of a network that are not directly visible, with profound applications in biological, social, and other complex systems. Despite intensive utilization of the topological feature in this task, it is unclear to what extent a feature can be leveraged to infer missing links. Here, we aim to unveil the capability of a topological feature in link … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 60 publications
0
1
0
Order By: Relevance
“…For instance, Jing et al found that understanding the inherent constraints imposed on data sets is crucial for evaluating the effectiveness of algorithms [17]. Similarly, Ran et al studied the effect of topological features on the theoretical limits of link prediction, providing valuable insights into how specific network topologies limit the effectiveness of prediction algorithms [18]. These studies underscore the importance of considering the intrinsic and topological characteristics of data when applying algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Jing et al found that understanding the inherent constraints imposed on data sets is crucial for evaluating the effectiveness of algorithms [17]. Similarly, Ran et al studied the effect of topological features on the theoretical limits of link prediction, providing valuable insights into how specific network topologies limit the effectiveness of prediction algorithms [18]. These studies underscore the importance of considering the intrinsic and topological characteristics of data when applying algorithms.…”
Section: Introductionmentioning
confidence: 99%